Training load, sports performance, physical and mental health during the COVID-19 pandemic: A prospective cohort of Swiss elite athletes - Karrer, Y.; Fröhlich, S.; Iff, S.; Spörri, J.; Scherr, J.; Seifritz, E.; Quednow, B. B.; Claussen, M. C. (PLOS ONE, 2022)
Background The COVID-19 pandemic and associated restrictions have led to abrupt changes in the lives of elite athletes. Objectives The objective of this prospective cohort study was to examine training load, subjective sports performance, physical and mental health among Swiss elite athletes during a 6-month follow-up period starting with the first Swiss lockdown. Methods Swiss elite athletes (n = 203) participated in a repeated online survey evaluating health, training, and performance related metrics. After the first assessment during the first lockdown between April and May 2020, there were monthly follow-ups over 6 months. Results Out of 203 athletes completing the first survey during the first lockdown, 73 athletes (36%) completed all assessments during the entire 6-month follow-up period. Sports performance and training load decreased during the first lockdown and increased again at the beginning of the second lockdown in October 2020, while symptoms of depression and financial fears showed only a transient increase during the first lockdown. Self-reported injuries and illnesses did not change significantly at any timepoint in the study. Stricter COVID-19 restrictions, as measured by the Government Stringency Index (GSI), were associated with reduced subjective sports performance, as well as lower training intensity, increased financial fears, poorer coping with restrictions, and more depressive symptoms, as measured by the 9-item module of the Patient Health Questionnaire-9 (PHQ-9). Conclusion This study revealed a negative impact of the COVID-19 restrictions on sports performance, training load and mental health among Swiss elite athletes, while the rate of self-reported injuries and illnesses remained unaffected.